HUBUNGAN KONTROL DIRI DENGAN KECANDUAN MEDIA SOSIAL (INSTAGRAM) PADA SISWA KELAS XI DI SMAS CAHAYA MEDAN - Regina Marenata Ketaren; Nuraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the relationship between self-control and social media addiction (Instagram) among students at SMAS Cahaya Medan. The sample comprised 218 students, selected using a total sampling technique that included all members of the population. A quantitative correlational research design was employed. Data were collected using two instruments: the Self-Control scale, developed based on Tangney's theory (2004), and the Social Media Addiction (Instagram) scale, based on Griffiths' theory (2014). The Self-Control scale contained 40 items with a reliability coefficient of 0.892, while the Social Media Addiction (Instagram) scale comprised 35 items with a reliability coefficient of 0.860. Data analysis utilized the Kolmogorov-Smirnov test and SPSS Statistics 25 for Windows. The asymptotic significance (2-tailed) value was 0.200, exceeding the threshold of 0.05. The analysis yielded a correlation coefficient (rxy) of -0.552 with a significance level of 0.000 (p < 0.05). The coefficient of determination (r2) was 0.304, indicating that 30.47% of the variance is explained. These findings demonstrate a significant negative relationship between self-control and social media addiction (Instagram) among eleventh-grade students at SMAS Cahaya Medan.